Empowering women in science: A good practice guide - De Tezanos Pintos, Paula (2025)
Empowerment can be thought of as a gain of power and autonomy by an unfavored group, which creates a better situation. Women in Science (WIS) face multiple barriers that ultimately affect their performance. There is an urgent need to reverse the inequalities and disadvantages that WIS face. With this aim, in May 2023, 17 WIS gathered in person for four days in a workshop entitled Empowering Women in Science. As an outcome of the workshop, we cooperatively started to draw up a list of empowerment recommendations. We continued working together for more than a year to improve this list, which we now present as the Good Practice Guide for Empowering Women in Science (GPG). The GPG contains recommendations across the individual, collective and system levels that we believe help address inequalities for WIS. The aim of this debate is twofold: a) to present the GPG and b) to use the GPG to self-evaluate the number of actions we, the authors, undertook before and after participating in the workshop. Results show that one year after ending the workshop, we doubled the number of actions performed across all categories assessed: I) identify, confront and make visible systemic barriers; II) self-promotion; III) promote other women, and IV) foster diversity, equity and inclusion. This suggests that empowerment can be fostered through formal training programs and discussion spaces. We hope that the GPG will inspire WIS across disciplines and backgrounds to: A) act towards empowerment (at the individual, collective and system level); B) embrace the notion that each of us can be part of the change that we want to see happening towards higher equity for WIS, and C) recognize that any action is better than inaction. Finally, the GPG provides a framework that will continue to be improved and expanded with the feedback of readers and users.